Frequency of the TMPRSS2:ERG gene fusion is increased in moderate to poorly differentiated prostate cancers. Issue 11 (26th January 2007) - Rajput, Ashish B; Miller, Melinda A; De Luca, Alessandro; Boyd, Niki; Leung, Sam; Hurtado-Coll, Antonio; Fazli, Ladan; Jones, Edward C; Palmer, Jodie B; Gleave, Martin E; Cox, Michael E; Huntsman, David G
Abstract : Background: Recent reports indicate that prostate cancers (CaP) frequently over-express the potential oncogenes, ERG or ETV1 . Many cases have chromosomal rearrangements leading to the fusion of the 5′ end of the androgen-regulated serine protease TMPRSS2 (21q22.2) to the 3′ end of either ERG (21q22.3) or ETV1 (7p21.3). The consequence of these rearrangements is aberrant androgen receptor-driven expression of the potential oncogenes, ETV1 or ERG . Aim: To determine the frequency of rearrangements involving TMPRSS2, ERG, or ETV1 genes in CaP of varying Gleason grades through fluorescence in situ hybridisation (FISH) on CaP tissue microarrays (TMAs). Methods: Two independent assays, a TMPRSS2 break-apart assay and a three-colour gene fusion FISH assay were applied to TMAs. FISH positive cases were confirmed by reverse transcriptase (RT) PCR and DNA sequence analysis. Results: A total of 106/196 (54.1%) cases were analysed by FISH. None of the five benign prostatic hyperplasia cases analysed exhibited these gene rearrangements. TMPRSS2:ERG fusion was found more frequently in moderate to poorly differentiated tumours (35/86, 40.7%) than in well differentiated tumours (1/15, 6.7%, p = 0.017). TMPRSS2:ETV1 gene fusions were not detected in any of the cases tested. TMPRSS2:ERG fusion product was verified by RT-PCR followed by DNA sequencing in 7/7 randomly selected positive cases analysed. Conclusion: This study indicates that TMPRSS2:ERG gene rearrangements in CaP may be used as a diagnostic tool to identify prognostically relevant sub-classifications of these cancers.